Resistive switching behaviour in ZnO and VO2 memristors grown by pulsed laser deposition. Issue 4 (1st February 2014) - Macaluso, R.; Mosca, M.; Costanza, V.; D'Angelo, A.; Lullo, G.; Caruso, F.; Calì, C.; Di Franco, F.; Santamaria, M.; Di Quarto, F.
Abstract : The resistive switching behaviour observed in microscale memristors based on laser ablated ZnO and VO2 is reported. A comparison between the two materials is reported against an active device size. The results show that devices up to 300 × 300 μm 2 exhibit a memristive behaviour regardless of the device size, and 100 × 100 μm 2 ZnO‐based memristors have the best resistance off/on ratio.